The Use of Illocutionary Speech Acts in Colloquial by Anak Dalam Jambi Tribe - Bambang Prastio; Istiqomah Nurzafira; Abd. Syukur Ibrahim; Gatut Susanto; Roekhan Roekhan (Masyarakat Linguistik Indonesia Universitas Andalas, 2020)
Anak Dalam Jambi Tribe (ADJT) lives in the forest, far from the population, and the existence is rare. This research aims to determine whether ADJT uses illocutionary speech act, function, and type of speech act used. This research uses qualitative with pragmatic research type. The data is in the form of an illocutionary speech act, which is then transcript by putting out the conversation context. This research's data source is from ADJT, who lives in Merangin Regency, Jambi Province, Indonesia. Result research shows that ADJT uses three types of speech acts, which are (1) directive with the function of prohibiting, ordering, and asking, (2) expressive with the function of thankful, and (3) commissive with the function of refusing. It can be concluded that ADJT frequently uses illocutionary to deliver information to interlocutors. This research is expected can become a preliminary step in further research, especially in the use of language related to indirect meaning in ADJT.